Efektifitas Media Panggung Boneka untuk Meningkatkan Kemampuan Bercerita pada Anak Usia Dini - Norma Diana Fitri (SELING: Jurnal Program Studi PGRA, 2015)
That basic background in this study is the lack of confidence of children by using storytelling so that the ability of language development is still considered the standard presentation said to be less than desirable, reaching 85%. Based on data from the early observations of researchers increased ability to tell a TK Permata Bunda Sidomukti Gresik grade A2 still unsatisfactory. Of the students who are 20 only 7 children (35%) were able to complete the tasks assigned by the teacher. To improve language skills by using the method of telling the researchers took measures of learning undertaken by two cycles. The formulation of the problem in this research are: (1) How can these media storytelling puppet stage in early childhood TK grade A2 Permata Bunda Sidomukti Gresik? (2) How to increase the ability of language development in the methods of telling stories using media puppet TK grade A2 Permata Bunda Sidomukti Gresik? To obtain the results of the study, the research conducted by collaborative methods between quantitative and qualitative. Quantitative methods produce data based on aspects of child development and qualitative methods generate data in the form of descriptions of observations interview. The model used is a model PTK Kurt Lewin in one cycle consists of four components, including: planning, action, observation, and reflection. The results showed that the use of media puppet to improve the ability of storytelling can improve learning achievement of children seen in the increase in the developmental aspects, namely in the first cycle is about 50%, then 90% in the second cycle.